2011
DOI: 10.1103/physrevlett.106.245701
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mixed-Mode Phase Transition Involving a Composition-Dependent Displacive Component

Abstract: Solid-solid displacive, structural phase transformations typically undergo a discrete structural change from a parent to a product phase. Coupling electron microscopy, three-dimensional atom probe, and first-principles computations, we present the first direct evidence of a novel mechanism for a coupled diffusional-displacive transformation in titanium-molybdenum alloys wherein the displacive component in the product phase changes continuously with changing composition. These results have implications for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 14 publications
6
57
0
Order By: Relevance
“…%) alloy [137]. The bcc β-phase to embryonic ω-phase transformation was recently clarified to occur through a displacive-diffusional process [138][139][140]. These authors demonstrated that the formation of ω-phase-like embryos occurred through competing compositional and structural instabilities arising in the bcc lattice of model binary Ti-Mo alloys during rapid cooling from the high-temperature single β-phase field.…”
Section: Agingmentioning
confidence: 99%
“…%) alloy [137]. The bcc β-phase to embryonic ω-phase transformation was recently clarified to occur through a displacive-diffusional process [138][139][140]. These authors demonstrated that the formation of ω-phase-like embryos occurred through competing compositional and structural instabilities arising in the bcc lattice of model binary Ti-Mo alloys during rapid cooling from the high-temperature single β-phase field.…”
Section: Agingmentioning
confidence: 99%
“…The combination of transmission electron microscopy (TEM) and atom probe tomography (APT) enables researchers to relate the atomic structure and composition of nanoscale features of interest and has been gaining influence over the past decades. Typically, correlative TEM/APT analyses have been carried out from distinct specimens from the same alloy, [1][2][3][4][5][6][7] which fails in cases where the microstructure is inhomogeneous and/or when targeting rare microstructural features for both TEM and APT investigations. As recently reviewed by Herbig,8 full electron microscopy characterization of specific features can be carried out on needle-shaped specimens prior to APT analysis by utilizing specially designed holders.…”
Section: Introductionmentioning
confidence: 99%
“…phase forms during ageing at temperatures below 823 K (Sikka et al, 1982;Ahmed et al, 2015). It also possesses a specific OR with the matrix (Furuhara et al, 2001) and produces diffraction spots at the 1/3{112} and 2/3{112} diffraction positions (Ng et al, 2011;Lai et al, 2015;Tane et al, 2013). As for the 0 (hexagonal) and the 00 (orthorhombic) phases, the two kinds of martensite, they generally form with an acicular or plate shape during rapid cooling from a temperature above or near T .…”
Section: Introductionmentioning
confidence: 99%